Sociodemographic and clinical characteristics of patients with violence attempts with psychotic disorders - Korkmaz, Sevda; Turhan, Levent; Izci, Filiz; Saglam, Sadullah; Atmaca, Murad (Modestum Ltd, 2017)
Objective: The objective of the study is to compare the socio-demographical characteristics of patients with psychotic disorders that engage or dont engage in violent behavior against individuals, and to conduct a research on the degree of affinity of the victims of violence with the patient and on factors that could affect violence. Methods: All patients (151 patients) that were treated during the last year, diagnosed with psychotic disorder. The patients were compared in two groups; these who engaged in violent acts and these who did not. Furthermore, patients in the violent group were separated into two groups; one consisting of the patients who engaged in violent behavior against immediate family members, hence the immediate violence group, and the patients who didn't engage in violence against immediate family members, hence the distant violence group. Results: It was determined that 56% of the patients with psychotic disorder have attempted violence, out of which 75% were engaged in violent behavior against their immediate relatives. It was determined that patients who attempted violence were primarily those diagnosed with paranoid schizophrenia and chronic schizophrenia. It was observed that patients that did not receive regular psychiatric therapy attempted in violence more than others. Conclusion: Patients with active psychotic symptoms should be treated in early stages and precautions should be taken against to decrease attempts at violence.
Keywords: schizophrenia; psychotic disorder; violence